Research Handbook of Employment Relations in Sport - Weststar, Johanna (Relations industrielles / Industrial Relations, 2019)
The article reviews the book, "Research Handbook of Employment Relations in Sport," edited by Michael Barry, James Skinner and Terry Engelberg.